Causes and consequences of intellectual migration of human capital in the context of national security: Public administrative aspect - Shpektorenko, Igor; Zahurska-Antoniuk, Victoriia; Pasichnyi, Roman; Ortina, Ganna; Orhiiets, Oksana; Pavlovskyi, Oleh (Edelweiss Applied Science and Technology, 2024)
The article considers theoretical and practical approaches to processes of the international intellectual migration and investigates modern processes of this phenomenon, their feature, the precondition and the reason at the present. The special attention is given to the role of intellectual migration of human capital on the landscape of national security of countries. It is shown that although the problem of intellectual migration of human capital, “brain drain”, previously attracted economists and sociologists, today it is in the center of attention of political scientists and researchers of international relations. The relationship between intellectual migration of human capital and soft power is considered.Potential vectors of public administration combatting negative consequences of intellectual migration of human capital within the plane of national security.